Differences in complications between colonoscopy and esophagogastroduodenoscopy in Japan using large-scale health insurance claims data - Yoshida, Naohisa; Ishikawa, Hideki; Mutoh, Michihro; Iwai, Naoto; Kobayashi, Reo; Inoue, Ken; Hirose, Ryohei; Dohi, Osamu; Itoh, Yoshito; Yoda, Azusa; Maeda-Minami, Ayako; Mano, Yasunari (Endoscopy International Open, 2025)
Analyses of colonoscopy (CS) and esophagogastroduodenoscopy (EGD) complications is crucial for further promoting use of endoscopy. This study analyzed rates of severe complications of CS compared with those of EGD using big data.As a study population, we retrospectively used commercially anonymized health insurance claims data covering 3,050,954 patients from January 2010 to December 2020. Patients ≥ 50 years old who underwent CS or EGD without treatment were included in the study. The main outcomes were differences in rates of hemorrhage, perforation, and fatal events between EGD and CS, and risk factors of each complication comparing CS with EGD.Among 290,470 CSs (male: 182,910, female: 107,560, median age [range]: 58 [50–75]) and 726,075 EGDs (male: 412,365, female: 313,710, 58 [50–75]), rates of hemorrhage, perforation, and fatal events for EGD and CS were 0.0069% vs. 0.0069% (P = 0.558), 0.0006% vs. 0.0024% (P = 0.008), and 0.00028% vs. 0.00034% (P = 0.648), respectively. Rates of hemorrhage for cases aged 50 to 64 and 65 to 75 years were 0.0059% vs. 0.0110% (P = 0.042) for EGD and 0.0061% vs. 0.0108% for CS (P = 0.264). Risks of hemorrhage for comparing CS to EGD were significant for biopsy (adjusted odds ratio [aOR] 95% confidence interval [CI] 2.75 [1.15–6.21]; P = 0.017) and antithrombotics (aOR 12.48; 95% CI 1.80–247.14; P = 0.026). Those for perforation were significant for ages 50 to 64 years (aOR 9.58; 95% CI 2.17–66.10; P = 0.006) and male sex (11.76 [1.85–222.65], P = 0.025).Compared with EGD, CS had a higher rate of perforation but not hemorrhage. Complication rates in CS did not differ by age.
Keywords: Endoscopy Lower GI Tract; CRC screening; Quality and logistical aspects; Performance and complications